德州市企业与国有企业比较分政及政策j'y = A comparative analysis of privately owned and state owned enterprises in Dezhou city and its policy implications - 刘长民 Liu, Changmin (2008)
The development of individual private enterprises had played an important role in Dezhou's economy, which is regarded as an undeveloped city in the eastern coastal areas in China. Through comparisons in efficiency between privately owned and state-owned enterprises, such as the capital and profit com tax rate, capital-output rate and labor-capital ratio, it is found that the privately owned enterprises are more efficient than the state-owned enterprises. It is therefore natural for Dezhou city to encourage the development of privately owned economy in order to achieve a high economic growth.